Some Contributions of Hittitology to Old Testament Study. The Tyndale Biblical Archaeology Lecture - Hoffner, H. A., Jr.
A Who were the Hittites of the Old Testament; B. Hittite law and the Old Testament; C. Hittite religion and the Old Testament; D. Hittite mythology and the Old Testament.